Bias-dependent spectral tuning in InP nanowire-based photodetectors. (17th February 2017) - Jain, Vishal; Heurlin, Magnus; Karimi, Mohammad; Hussain, Laiq; Aghaeipour, Mahtab; Nowzari, Ali; Berg, Alexander; Nylund, Gustav; Capasso, Federico; Samuelson, Lars; Borgström, Magnus T; Pettersson, Håkan
Abstract: Nanowire array ensembles contacted in a vertical geometry are extensively studied and considered strong candidates for next generations of industrial scale optoelectronics. Key challenges in this development deal with optimization of the doping profile of the nanowires and the interface between nanowires and transparent top contact. Here we report on photodetection characteristics associated with doping profile variations in InP nanowire array photodetectors. Bias-dependent tuning of the spectral shape of the responsivity is observed which is attributed to a Schottky-like contact at the nanowire–ITO interface. Angular dependent responsivity measurements, compared with simulated absorption spectra, support this conclusion. Furthermore, electrical simulations unravel the role of possible self-gating effects in the nanowires induced by the ITO/SiO x wrap-gate geometry. Finally, we discuss possible reasons for the observed low saturation current at large forward biases.